THE EFFECT OF COMPETENCE, COMMUNICATION AND MOTIVATION ON PERFORMANCE OF BATAM UTARA TAX OFFICE’s EMPLOYEE - Setiyowati, Herny; Indrayani, Indrayani; Ngaliman, Ngaliman; Ngalimun, Ngalimun (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
Employees in carrying out their duties and functions are expected to provide the performance expected by the organization. The elements that affect performance include employee competence, communication and employee motivation in carrying out their duties and functions. This condition is also expected to give the same result to the Batam Utara Tax Office. To determine the effect of competence, communication, motivation on the performance of the employees of the Batam Utara Tax Office. The sample of the study amounted to 50 people, this study obtained the results Y = 7.582 + 0.036x1 + 0.414x2 + 0.293x3 +e. With an R2 value of 0.625 (62.5%). The competence variable has an insignificant positive effect on performance of 0.036, a significant level of 0.829 is greater than 0.05, the hypothesis Ho is rejected and Ha is accepted, the conclusion is the hypothesis is rejected. the hypothesis Ha is accepted and Ho is rejected, the conclusion of the hypothesis is accepted. motivation has a significant effect on work performance of 0.293 significant level 0.033 smaller than 0.05 the hypothesis Ha is accepted and Ho is rejected, the conclusion is the hypothesis is accepted. Competence, communication and motivation affect employee performance Simultaneous Test (F test) of 17.809 with a significant value of 0.000 where the value is smaller than 0.05. Hypothesis Ho is rejected and Ha is accepted.